Organizing Evidence Based Medicine (EBM) Journal Clubs in Department of Neurosurgery, Tabriz University of Medical Sciences - Shokouhi, Ghaffar; Ghojazadeh, Morteza; Sattarnezhad, Neda (International Journal of Health Sciences, 2012)
Introduction: A journal club is a group of individuals who meet regularly to evaluate critically the clinical application of latest medical literature. Evidence-based medicine (EBM) is ‘the use of current best evidence, in making decisions about the care of individual patients’. For this purpose, we organized journal clubs using standard EBM method, to substitute for traditional ones, evaluating efficacy of evidence based meetings in improvement of medical education in department of Neurosurgery. Methods and Materials: After six traditional journal clubs two validated questionnaires (evaluating organizing method and degree of satisfaction), were filled out by the residents. After an instructing workshop and six evidence based journal sessions, the same questionnaires were completed by the attendees. The collected data were analyzed using SPSS 17. Results: The mean score of the first questionnaires (Evaluating the method of organizing sessions) 16.72±7.86 (median=14) for traditional journal clubs and 40.18±6.38 (median=40) for evidence based forms (P=0.003).The mean grade of the second questionnaires (degree of satisfaction) was 13.18±4.6 (median=14) and 21.90±4.27 (median=22), for traditional and evidence based ones, respectively. (P=0.006). Conclusion: The aim of evidence based journal club is to help individuals to evaluate the current literature critically. The best way to decide if any adjustments are necessary is to ask the participants whether they are satisfied with the conference. As improvement of critical judgment is the goal of the journal clubs, the response of the resident according to the knowledge of methodology and biostatistics, is a principle. In present study, significant improvement in critical appraisal skills was seen after holding evidence based journal clubs. Key Words: Journal Club, EBM, Neurosurgery